Derivadas de Polinomios

Calcula la derivada de las siguientes funciones:

- a) y = 3x^4
- b) f(x) = -2x^5
- c) y = 3x^{-2}
- d) f(x) = \frac{2}{3}x^4 - 4x^3
- e) y = 4x^3-5x
- f) f(x) = -2^4+3x^2-x+1
- g)y= -3x^{-4}
- h) f(x)= 2x^{-3}-3x^{-1}

SOLUCIÓN

- a) y = 3x^4

y\textsc{\char13}=12x^3

- b) f(x) = -2x^5

f\textsc{\char13}(x)=-10x^4

- c) y = 3x^{-2}

y\textsc{\char13}=-6x^{-3}

- d) f(x) = \frac{2}{3}x^4 - 4x^3

f\textsc{\char13}(x)= \frac{2}{3} \cdot 4x^3-12x^2

- e) y = 4x^3-5x

y\textsc{\char13}=12x^2-5

- f) f(x) = -2^4+3x^2-x+1

f\textsc{\char13}(x)=6x-1

- g)y= -3x^{-4}

y\textsc{\char13}=12x^{-5}

- h) f(x)= 2x^{-3}-3x^{-1}

f\textsc{\char13}(x)=-6x^{-4}+3x^{-2}